Response of Pembrolizumab Alone for Non-small Cell Lung Cancer With Brain Metastasis: A Case Report and Literature Review - Marvin, Eric A.; Furrow, Kimberley L.; Kar, Ayesha; Cuoco, Joshua A. (Frontiers in Oncology, 2020)
Treatment of brain metastases often includes surgical resection, chemotherapeutics and radiotherapy. Given the difficulty in obtaining therapeutic levels of medications within the immune-privileged central nervous system, chemotherapy as a stand-alone treatment modality for brain metastases is an uncommon option. However, there is a growing body of evidence to suggest that immunomodulatory agents can induce a robust immune response in the central nervous system. Here, we describe a 68-year old male who presented with radiographic evidence of new and enlarging lung nodules with mediastinal adenopathy. Lung biopsy was consistent with adenocarcinoma. Immunohistochemical staining demonstrated high expression of programmed cell death protein 1 with a tumor proportion score of 100%. Surveillance magnetic resonance imaging of the brain demonstrated a single enhancing 11 x 7 x 12mm lesion along the mesial surface of the right frontal lobe. The patient deferred surgical resection as well as stereotactic radiosurgery but agreed to treatment with pembrolizumab. Repeat magnetic resonance imaging at three-months after initiation of treatment demonstrated complete radiographic resolution of the brain lesion. To our knowledge, this is one of only a few reports in the current literature to document complete resolution of non-small cell lung cancer brain metastasis with pembrolizumab alone. We discuss the emerging literature regarding the efficacy of pembrolizumab in the treatment of brain metastases, central nervous system penetration and emerging new treatment paradigms involving novel immunotherapy agents.